The Role and Importance of Human Capital in Increasing the National Wealth of The Country (Eurasian Journal of History, Geography and Economics, 2024)
This article examines the role and importance of human capital in the development of the country’s economy. Also, information about the share of human capital in the national income of Uzbekistan and developed countries.